STUDY OF THE BOOK OF TAFSIR MA'ALIM AT TANZIL BY AL BAGHAWI - Fariz Wiradasa Bhekti Nugrahadi (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
There are verses in the Qur'an that we can understand directly, and there are those that require further explanation. To make it easier to understand what the Qur'an conveys, we need interpretations from experts. So understanding the matter of interpretation is a step that should not be skipped by a Muslim. Therefore, in this article, the author wants to dissect one of the products of interpretation, namely Ma’alim At-Tanzil by Al-Baghawy. This article aims to dissect the book of interpretation by Ma'alim At-Tanzil by explaining various aspects of the book. The author uses the literature study method to collect the data needed for this writing. This article will describe, starting from the background of writing the book of interpretation, the method of interpretation, the style of interpretation, the characteristics of the book, the way of presentation used by Al-Baghawy, as well as the advantages and disadvantages of the book. The results explain that this monumental book of interpretation is very closely related to linguistic and fiqh features; also, Al-Baghawy, in his interpretation, combines the methods of interpretation bil ma'tsur and bil ra'yi. The Ma'alim At-Tanzil has many advantages and only a few shortcomings that do not damage the results of its interpretation.